PHARMACOECONOMIC ANALYSIS OF TREATMENT OF OUT-OF-HOSPITAL COMPLICATED ABDOMINAL INFECTIONS WITH NEW-GENERATION CARBAPENEM — ERTAPENEM - A.S. Kolbin; Yu.B. Belousov; S.V. Sidorenko; K.A. Goryachkina; O.A. Koroleva; D.Yu. Belousov; N.N. Klimko (Педиатрическая фармакология)
In a surgeon’s practice, complicated intra-abdominal infections (CII) are one of the most frequent nosological entities. E. Proteus spp., Klebsiella spp. are considered to be leading activators of out-of-hospital CII. For the first time in a Russian economic environment the authors, using mathematical modeling methods, have conducted a clinical and economic research of the new carbapenem, ertapenem, for monotherapy of complicated intra-abdominal infections. They have calculated the total cost, including the cost of CII treatment subject to indicators such as efficiency of treatment and infection-related probability of death (attributive lethality). Results of the «susceptible-infected-susceptible» model were used to assess the impact of acquired bacterial resistance on the efficacy of treating complicated intra-abdominal infections. As a result it was found that in the case of out-of-hospital complicated intraabdominal infections, it is more advisable from the clinical and economic standpoint to start treatment with ertapenem; less advisable is to start with the combination of ceftriaxone and metronidazole or the combination of ciprofloxacin and metronidazole. Key words: clinical and economic analysis, ertapenem, complicated intra-abdominal infections, resistance. (Pediatric Pharmacology. – 2010; 7(1):29-40)